2003
DOI: 10.1046/j.1523-1747.2003.12016.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 Promoter Polymorphisms and Susceptibility to Skin Squamous Cell Carcinoma After Renal Transplantation

Abstract: After organ transplantation, susceptibility to cancer is multifactorial, especially for skin carcinomas. Risk factors may include genetic susceptibilities, such as the control of cytokine production. Interleukin-10 is a cytokine that is implicated in tumorigenesis, and it has been shown that polymorphisms in its gene promoter correlate with differential amounts of production. The aim of this study was to investigate a possible association between interleukin-10 gene promoter polymorphisms and the occurrence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 33 publications
(32 reference statements)
0
33
0
2
Order By: Relevance
“…Therefore, we hypothesized that IL-10 expression in CC can be associated with HPV infection, and this could produce an immunosuppressive microenvironment and accelerates tumor growth. has been reported that several important polymorphic sites in the IL-10 gene, appears to be responsible with modulated levels of IL-10 [11][12][13]. The association of IL-10 promoter SNPs with CC has been reported by several studies, but with inconclusive findings [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we hypothesized that IL-10 expression in CC can be associated with HPV infection, and this could produce an immunosuppressive microenvironment and accelerates tumor growth. has been reported that several important polymorphic sites in the IL-10 gene, appears to be responsible with modulated levels of IL-10 [11][12][13]. The association of IL-10 promoter SNPs with CC has been reported by several studies, but with inconclusive findings [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…24,25 The IL10 gene has been implicated in the response to a number of diseases such as hepatitis B, pulmonary tuberculosis, herpes zoster, cutaneous malignant melanoma, hepatocellular carcinoma fibrosis, gastric carcinoma, squamous cell carcinoma, inflammatory bowel disease, and HIV. [26][27][28][29][30][31][32][33][34] The genetic neighbors of IL10 consisting of IL19, IL20, and IL24 also modulate the TH1 and TH2 response, suggesting that these recently discovered loci could also be important in HCV clearance. 35 A number of studies have examined the IL10 promoter region SNPs and their associations with HCV susceptibility as well as resistance to antiviral therapy.…”
Section: Introductionmentioning
confidence: 99%
“…This observation complements the preference of a proinflammatory environment for the development of aggressive BCC. When studying squamous and BCCs Alamartine et al 19 reported that high levels of IL-10 and the corresponding promoter polymorphism were associated with SCC and not with BCC. Our pilot study, albeit a small number of aggressive BCC, has shown that a cytokine genetic profile corresponding to a proinflammatory environment with increased TNF-a concomitant with a decrease in antiinflammatory IL-10 is more prevalent in aggressive BCC.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies on BCC have investigated the role of the TNF-308 G à A polymorphism and the IL-10 gene. 19 These studies reported that the TNF allele haplotype a2b4d5 associated with increased transcription significantly influenced the number of BCC tumors in an individual. 17 In an effort to link the LOH at 9q22 and the presence of TNF-a 2308 and IL-10 21082 polymorphisms to aggressive BCCs, we examined the DNA from 15 nonaggressive and 6 discerningly chosen, aggressive BCCs that were microdissected from formalin-fixed paraffin-embedded tissue sections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation